(untitled) (International Journal of Engineering Sciences & Management Research, 2016)
The Cement concrete is widely used now-a-days for general as well as massive structures. There may be a situation, which leads to the stoppage in the production of cement due to the lack of lime which is going on reducing in the quarries for many other beneficial uses. So replacement of cement is necessary either completely or partially for further making of new products. Experiments are being conducted using different materials which are naturally available and by products obtained from industries trying for the efficient and safe result. Our project is one of those trials which deal with the partial replacement of cement with coal dust and iron rust. Coal dust and iron rust are naturally available materials formed by the disintegration of coal and iron respectively. The compressive strength of M20 grade concrete is tested with 5%, 10%, 15% and 20% replacements for 7 days and 14 days and compared accordingly.